Small Bites - Big Threats: Prevalence of scrub typhus among the pediatric population in a rural tertiary care hospital in South India - B, Rajkumar; Aasaithambi, Anupriya; A, Uma; N, Prabhusaran (Tropical Journal of Pathology and Microbiology, 2020)
Background: It is an acute, febrile, exanthematous illness with a high fatality rate. Scrub typhus is underdiagnosed in India due to its non-specific clinical presentation, limited awareness, and low index of suspicion among clinicians and lack of diagnostic facilities. Objective: This study was carried out to know the seroprevalence of scrub typhus in clinically suspected children and to compare a rapid test which is a simple and economic test with IgM ELISA for the diagnosis of scrub typhus. Methods: This cross-sectional analytical study was conducted from a period of three months. The study population comprised mainly 140 young children attending Pediatric OP and in patients admitted to a tertiary care teaching hospital with fever and related symptoms. A serum sample was tested for Weil Felix reaction, IgM ELISA, and rapid card test. Results: The mean age group of the study population is 7 to 9 years, of which seven cases were positive. The major predisposing factor for scrub typhus infection was vegetation around houses. The sensitivity and specificity of both card test and IgM ELISA was 100%. Conclusion: In this study, 5% of febrile children were positive for scrub typhus. Leptospirosis, Dengue, and Typhoid were the common co-infections found in scrub typhus, positive children. Scrub typhus should be included in the differential diagnosis of fever of unknown origin in children.